A critical review on sintering and mechanical processing of 3Y-TZP ceramics. Issue 2 (15th January 2023) - Yin, Youkang; Xu, Jinyang; Ji, Min; Li, Linfeng; Chen, Ming
Abstract: Zirconia ceramics have been extensively applied in dental restoration due to their superior properties and excellent functionalities. Green-compact sintering and mechanical processing have become critical operations to shape these denture materials to target dimensions and desired quality. Improper sintering regulations and cutting-induced damages are crucial issues when dealing with the manufacturing of ceramic dentures as they adversely affect the performance and acceptance of eventually-machined denture products. In this paper, a critical review has been conducted to offer a scientific understanding of 3 mol% yttria-stabilized tetragonal zirconia polycrystal (3Y-TZP) processing, focusing on illustrating the characteristics and properties of the materials as well as the influence of the sintering process on the microstructure and machinability of the workpiece. Recent advances addressing the processing issues of zirconia ceramics for dental applications are carefully reviewed by critically analyzing the scientific findings reported in the open literature. The fundamental influences of the working conditions on the machining quality of ceramic materials are discussed. The features of emerging non-traditional machining technologies are compared and analyzed. Dentures manufacturers will benefit from this review article as they seek to achieve high-quality processing for zirconia ceramics.